Ethical and Legal Implications of AI in Decision-Making - Zahra, Y; Amirah (PT. Lentera Ilmu Publisher, 2024)
This study explores the ethical and legal implications of integrating artificial intelligence (AI) into decision-making processes across various industries. As AI systems become increasingly prevalent, concerns arise regarding their transparency, fairness, and accountability. The study reviews examples from healthcare, finance, criminal justice, human resources, and retail to highlight issues such as bias, lack of transparency, and privacy concerns. Current regulations often inadequately address the unique challenges posed by AI, particularly regarding accountability and the ethical use of personal data. By developing a comprehensive framework that integrates ethical principles—such as fairness, justice, and autonomy—with legal concepts like liability and data protection, the study proposes practical solutions to mitigate these risks. The findings underscore the need for enhanced oversight, rigorous validation, and transparent practices to ensure AI systems are used responsibly, thereby aligning technological advancements with ethical and legal standards.